Detection of Sugarcane Leaf Disease Using Pre-Trained Feature Extraction and SVM Method - Izza, Mufidatul; Lutfi, Moch. (Journal of Applied Informatics and Computing, 2025)
Sugarcane (Saccharum officinarum) is an important commodity in the sugar industry, but it is vulnerable to leaf diseases such as Red Rot, Rust, Yellow Leaf, and Mosaic, which can significantly reduce the quality and quantity of yields. Manual identification is time-consuming and prone to subjective errors, therefore an automatic detection method based on digital images is required. This study proposes a combination of VGG16 pre-trained as a feature extractor with Support Vector Machine (SVM) as a classifier. The dataset used is the Sugarcane Leaf Disease Dataset from Kaggle, consisting of 2,521 images of five classes, which were then balanced through augmentation in the form of rotation, zoom, and flipping to a total of 3,000 images (600 per class). The preprocessing stage includes resizing the images to 224×224 pixels and normalization using the preprocess_input function. Three model scenarios were tested, namely SVM, VGG16, and VGG16+SVM. Evaluation was carried out using two methods, namely an 80:20 train–test split and 10-fold cross-validation, with metrics of accuracy, precision, recall, F1-score, G-Mean, and AUC. The experimental results show that VGG16+SVM provides the best performance with an accuracy of 99.60% on the 80:20 scheme, while on 10-fold cross-validation the average accuracy is 80.76%. This value surpasses the baseline SVM and VGG16 + Softmax, proving that the integration of VGG16 feature extraction with SVM classification can produce stable and accurate performance. This research contributes to the development of image-based plant disease detection systems to support precision agriculture and fast decision-making.